Decolonizing the Literature Classroom. (September 2020) - Noyes, John K.
Abstract : What does it mean to decolonize the literature classroom? This short paper is intended as a personal reflection on teaching as an engagement with the social forces that bring neocolonial relations into the classroom, drawing on my experience teaching literature and literary theory in South Africa and Canada. I explore the idea of decolonizing the classroom as the production of an "outside" that provides meaning for the classroom's "inside."